USING TIKTOK SOCIAL MEDIA AS A MARKETING PROMOTION MEDIA IN ONLINE BUSINESS - Moch Anton Maulana; Novi Sri Sandyawati (International Journal of Social Science, 2023)
TikTok Marketing or TikTok Marketing is the activity of using the social media platform TikTok. There are many different strategies you can use to maximize your marketing, such as creating engaging and viral organic content, running TikTok ads, and more. TikTok as a viral media now has great potential as an advertising medium for each of our products. In fact, using TikTok is not just a means of entertainment but can also be used as a digital marketing strategy that is useful for increasing public awareness and even increasing your business income through creative content. By projecting films, pictures and songs, this tool facilitates the transmission of information and can explain stimuli to those who watch, imitate/broadcast them. The aim of this research is to determine the extent to which a company's digital marketing activities use the Tik Tok social network. The observation method used in the research here uses qualitative observation with descriptive strategies and questionnaire data collection techniques. This research analysis method is applied after the data is generated through a questionnaire and then analyzed together to produce temporary hypotheses and draw conclusions. The observations obtained show that he uses social networks to market his business on Instagram, so that gradually he is starting to become known and many of his customers are marketing their products through digital commerce, which means this can be seen very easily by social media users. on their products posted on their Instagram and enjoy. A TikTok account is an advertising tool to attract customers on social networks, so it will have an impact on increasing monthly income